Speed Variation along an Imposed Linear Trajectory, for Robotic Arms Motion - Matica, Liliana Marilena; Kovendi, Zoltan; Gergely, Eugen; Coroiu, Laura (International Journal of Engineering and Management Sciences, 2019)
The paper describes a method of speed (velocity) computation, named mixt profile, during a motion upon an imposed linear trajectory. The method assures an accurate positioning at the end of motion (movement), in a well determinate time lapse. The described method is linked with position vector computation, about a robotic arm.